The Role of Instructional Design in Improving Pre-Service and In-Service Teacher’s Mathematics Learning Sets Skills: A Systematic Literature Review in Indonesian Context - Naufal Ishartono; Rafiza binti Abdul Razak; Siti Hajar binti Halili; Yoga Dwi Windy Kusuma Ningtyas; Wilda Syam Tonra; Muhammad Noor Kholid; Mohamad Waluyo; Soraya Djamilah (Universitas Muhammadiyah Surakarta, 2023)
Several previous researchers have tried to review the results of previous research related to the development of learning tools using a systematic literature review (SLR) model. However, SLR research efforts that examine the development of learning tools carried out by Indonesian in-service and pre-service mathematics teachers are still limited. Therefore, this study seeks to answer two questions, namely (1) what is the mathematics learning sets developed by the Indonesian ISTs and PSTs, and (2) What instructional design model is used by the Indonesian ISTs and PSTs in developing mathematics learning sets. As many as 55 articles were selected using the PRISMA protocol by retrieving articles from the ERIC and Dimensions databases. The findings of the two questions are that the ADDIE model is the most widely used model by Indonesian PSTs and ISTs in developing learning sets. In addition, mathematics learning media and mathematics student worksheets are the most developed tools by authors. This study also examines several instructional designs and types of mathematics learning sets developed by researchers, which can undoubtedly be a refer-ence for subsequent researchers in developing mathematics learning sets.